Simulating spatiotemporal variability of blue and green water resources availability with uncertainty analysis. Issue 8 (22nd September 2014) - Zuo, Depeng; Xu, Zongxue; Peng, Dingzhi; Song, Jinxi; Cheng, Lei; Wei, Shouke; Abbaspour, Karim C.; Yang, Hong
Abstract Due to rapid socioeconomic development, continuous population growth and urbanization, the world is facing a severe shortage of fresh water, particularly in arid and semi‐arid regions. A lack of water will put pressure on agricultural production, water pollution, as well as eco‐environmental degradation. Traditional water resources assessment mainly focused on blue water, ignoring green water. Therefore, analysis of spatiotemporal distribution of blue and green water resources in arid and semi‐arid regions is of great significance for water resources planning and management, especially for harmonizing agricultural water use and eco‐environmental water requirements. This study applied the Soil and Water Assessment Tool (SWAT) model and the Sequential Uncertainty Fitting algorithm (SUFI‐2) to calibrate and validate the SWAT model based on river discharges in the Wei River, the largest tributary of the Yellow River in China. Uncertainty analysis was also performed to quantify the blue and green water resources availability at different spatial scales. The results showed that most parts of the Wei River basin (WRB) experienced a decrease in blue water resources during the recent 50 years with a minimum value in the 1990s. The decrease is particularly significant in the most southern part of the WRB (the Guanzhong Plain), one of the most important grain production bases in China. Variations of green water flow and green water storage were relatively small both on spatial and temporal dimensions. This study provides strategic information for optimal utilization of water resources in arid and semi‐arid river basin. Copyright © 2014 John Wiley & Sons, Ltd.